Cannabis use among patients with cutaneous lymphoma: A cross-sectional survey. (August 2022) - Mahurin, Heather M.; Ware, Olivia R.; Coolman, Tyler D.; Stevenson, Philip A.; Pergam, Steven A.; Shinohara, Michi M.
Abstract: Objectives: To evaluate patterns of cannabis use in patients with cutaneous lymphoma (CL), as well as the association between cannabis use and itch specifically. Design: Cross-sectional survey created in partnership with the Cutaneous Lymphoma Foundation (CLF). Setting: The online survey was distributed electronically via email to the CLF listserv and links posted to social media over a 2-week period. Main outcome measures: Respondents were classified as current cannabis users, prior users, and never users. A visual analog scale (VAS) was used to assess itching severity, improvement of itch, and interest in learning about cannabis. Results: A total of 119 patient responses (61% female, mean age 59 y) were included in analysis. The majority had mycosis fungoides or Sézary syndrome (74%; 88/119) and early stage (IA-IIA) disease (56%; 48/86). Mean VAS itch score was 3.2 + 2.8 for the cohort. Over half (55%; 60/110) reported ever having used cannabis, with 22% (24/110) endorsing current cannabis use. Common methods of cannabis use were smoking (54%) and vaporizing (46%). 25% (6/24) of current users reported using cannabis specifically to treat itch; these respondents noted that cannabis resulted in moderate improvement of itching (mean 6.6/10). There was strong interest in learning more about cannabis and cancer, and most desired this information from their CL doctor/nurse. Conclusions: Cannabis use is common among patients with CL, and patients report improvement of itching as a result of using cannabis. Further studies are needed to elucidate the risks and benefits of cannabis use in this patient population. Highlights: Cannabis use is common among patients with cutaneous lymphoma (CL). A subset of patients reported cannabis use specifically to treat itch. Those who had used cannabis for itch noted moderate improvement of their symptoms. Most patients desired more information about cannabis and cancer from CL providers.